THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY AS A LEGAL OBLIGATION FOR PLANTATION COMPANIES IN SELUMA REGENCY - M. Alvin Azhari; Widiya N. Rosari; Candra Irawan (Universitas Bengkulu, 2021)
This study aimed to examine and analyze the implementation of corporate social responsibility as a legal obligation for plantation companies in Seluma Regency carried out by PTPN VII of Padang Pelawi Business Unit. The type of this study was juridical empirical with descriptive research design. The results of this study indicated that the implementation of CSR by PTPN VII of Padang Pelawi Business Unit had been carried out with the Partnership and Community Development Program (known as PKBL in Indonesian abbreviation) based on the State-Owned Enterprise Ministerial Regulation Number: 09/MBU/07/2015 concerning the Partnership and Community Development Program for State-Owned Enterprises and its amended regulations. However, it had not been running optimally. Matters that need to be revised and improved besides continuing to implement the PKBL program that have been carried out were continue to enhance other CSR activities, especially those related to efforts to improve community welfare by increasing business capital assistance in the Partnership Program, and to provide access to information as well as to establish communication with the community so that CSR objectives can be more optimal.